Role of Resource-based View in Predicting ERP Perceived Value: Higher Education Perceptions - Soliman, Mohamed; Karia, Noorliza (Journal of Technology Management and Business, 2021)
Higher education institutions (HEIs) nowadays focus on using strategic information systems as part of their digital strategy. An Enterprise Resource Planning (ERP) system can help HEIs manage their resources and operations effectively to meet this challenge. Based on reviews, this study conceptualizes the influential ERP factors into the resource-capability configuration. A preliminary study on ERP among 40 HEIs in Egypt was carried out for the Egyptian HEIs to explore their perception of the ERP system as a new integrating tool for their value and advantage. The results revealed that a high percentage of HEIs had not yet adopted these systems, despite their positive attitude towards the value of ERP systems. They are still at the developing level because these systems have not yet been adopted. This study also helps to advance ERP concepts and provides practical verification in the context of higher education. Finally, this research guide HEIs to understand the ERP system’s necessity as a strategic system proposing them to adopt ERP systems for their competitiveness.